(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article explores the innovative concept of "Manga Administrative Management" in the context of preschool education, focusing on how manga (Japanese comic art) and its principles can be applied to improve administrative processes, communication, and organizational efficiency in early childhood education settings. By integrating manga into administrative practices, this approach seeks to engage educators, children, and parents in a more interactive and visually appealing way. The article discusses the potential benefits of using manga for visual communication, staff training, community engagement, and policy dissemination in preschools. Additionally, it evaluates the challenges and practical considerations of applying manga-based strategies to preschool management.